Gasless Laparoscopic Surgery plus Abdominal Wall Lifting for Giant Hiatal Hernia——Our Single-center Experience - 余江洪 伍冀湘 于磊 李建业 (Journal of Huazhong University of Science and Technology. Medical sciences, 2016)
Giant hiatal hernia（GHH） comprises 5% of hiatal hernia and is associated with significant complications.The traditional operative procedure,no matter transthoracic or transabdomen repair of giant hiatal hernia,is characteristic of more invasion and more complications.Although laparoscopic repair as a minimally invasive surgery is accepted,a part of patients can not tolerate pneumoperitoneum because of combination with cardiopulmonary diseases or severe posterior mediastinal and neck emphesema during operation.The aim of this article was to analyze our experience in gasless laparoscopic repair with abdominal wall lifting to treat the giant hiatal hernia.We performed a retrospective review of patients undergoing gasless laparoscopic repair of GHH with abdominal wall lifting from 2012 to 2015 at our institution.The GHH was defined as greater than one-third of the stomach in the chest.Gasless laparoscopic repair of GHH with abdominal wall lifting was attempted in 27 patients.Mean age was 67 years.The results showed that there were no conversions to open surgery and no intraoperative deaths.The mean duration of operation was 100 min（range：90–130 min）.One-side pleura was injured in 4 cases（14.8%）.The mean postoperative length of stay was 4 days（range：3–7 days）.Median follow-up was 26 months（range：6–38 months）.Transient dysphagia for solid food occurred in three patients（11.1%）,and this symptom disappeared within three months.There was one patient with recurrent hiatal hernia who was reoperated on.Two patients still complained of heartburn three months after surgery.Neither reoperation nor endoscopic treatment due to signs of postoperative esophageal stenosis was required in any patient.Totally,satisfactory outcome was reported in 88.9% patients.It was concluded that the gasless laparoscopic approach with abdominal wall lifting to the repair of GHH is feasible,safe,and effective for the patients who cannot tolerate the pneumoperitoneum.